A sensitive solid-phase assay for identification of class A macrophage scavenger receptor ligands using cell lysate. - Plüddemann, A; Neyen, C; Gordon, S; Peiser, L (2008)
In order for macrophages to perform their numerous homeostatic, immunological and tissue remodeling functions they are required to express a broad repertoire of cell-surface receptors. These receptors are particularly important for their host-defense functions in the recognition of foreign pathogens. Delineation of the particular functions of specific receptors requires the identification of ligands recognized by the receptor. We have developed a sensitive, high throughput, solid-phase assay for the detection of ligands for the class A macrophage scavenger receptor (SR-A). Post-nuclear cell lysate from murine bone marrow-derived macrophages is used as a source of receptor and specific ligand binding to SR-A is detected with a monoclonal antibody for SR-A. This assay has been used effectively to identify protein ligands for SR-A on the surface of the bacterium Neisseria meningitidis (Peiser, L. et al. [Peiser, L., Makepeace, K., Pluddemann, A., Savino, S., Wright, J.C., Pizza, M., Rappuoli, R., Moxon, E.R., Gordon, S., 2006. Identification of Neisseria meningitidis nonlipopolysaccharide ligands for class A macrophage scavenger receptor by using a novel assay. Infect. Immun. 74, 5191-5199]). In this paper we describe the method in detail and define the specific variables governing the assay.